Pentingnya Pendidikan Karakter pada Anak Sekolah Dasar di Era Digital - Sri Rejeki (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This article uses a meta-analysis method to investigate the extent to which character education in elementary schools, especially in the digital era, plays a role in forming a quality generation. This research uses a meta-analysis approach with a focus on qualitative research that has been conducted previously. A qualitative research design, through case studies, was used to understand the experiences, perceptions and effectiveness of character education for elementary school children in the digital era. The research population involved elementary school students, parents, and teachers. The sample was selected purposively by taking into account variations in characteristics such as age, gender and socio-economic background. Data was collected through interviews, observation and documentation. Interviews were conducted with teachers, parents and students. Observation involves observing the implementation of character education in the school environment. Data is also collected through documentation of character education activities that have been implemented. Research shows that character education for elementary school children in the digital era has a positive impact in shaping children's character. Integrating character education material into subjects, self-familiarization activities, and creating a conducive school environment are effective strategies